Impacts of the Covid-19 pandemic on the coffee production and marketing system: a study of a family business in south Minas Gerais (Research, Society and Development, 2021)
To avoid COVID-19 contamination among humans, it is also necessary to increase hygiene practices, the use of masks and social distancing. All of this implies changes in work, consumption, employment and the economy. Many companies are unable to produce and market to avoid causing agglomerations, so the lack of production and sales is causing a decrease in income. This impacts all production sectors, both urban and rural. This work aims to investigate the effects of the COVID-19 pandemic on the production and marketing system of coffee grown by a family business in the coffee sector installed in the municipality of Santa Rita do Sapucaí, Minas Gerais. Using the narrative interview as a research method, concluded that company managers are regularly adopting COVID-19 prevention techniques, the pandemic affected the business in several positive and negative aspects, among them, it caused them to face several challenges to stay in the market and reorganize the work carried out by employees; and as a positive points, the company was directed to focus your business for the coffees they produce, in the provision of services and brand promotion.